2007
DOI: 10.3748/wjg.v13.i40.5380
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofH pyloritherapy on erythrocytic and iron parameters in iron deficiency anemia patients withH pylori-positive chronic gastristis

Abstract: AIM: To elucidate the influences of H pylori infection on oral iron treatment for iron deficiency anemia (IDA). METHODS:A total of 86 patients were divided into two groups: group A, receiving ferrous succinate combined with triple therapy for H pylori eradication, and group B (control), treated with ferrous succinate only. During treatment of IDA, dynamic changes in hemoglobin (Hb) level, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), serum iron (SI), and serum ferritin (SF) were compared be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 22 publications
3
49
0
3
Order By: Relevance
“…[8] . Also Chen and Lue, 2007 reached the same result although the study was in non-pregnant females [16] .…”
Section: Discussionsupporting
confidence: 64%
“…[8] . Also Chen and Lue, 2007 reached the same result although the study was in non-pregnant females [16] .…”
Section: Discussionsupporting
confidence: 64%
“…3 In certain geographic areas, intestinal parasites, particularly hookworm, worsen the iron deficiency because of blood loss from the gastrointestinal tract. 4,5 It is important economically, because IDA diminishes the capability of individuals in peripheral countryside living areas of rapidly developing countries like China, India and Pakistan to perform physical labor as their source of income, and it diminishes both growth and learning in children.…”
Section: Introductionmentioning
confidence: 99%
“…A total of seven studies were selected for review of the full paper and data extraction [7][8][9][10][11][12][13]. The high clinical heterogeneity detected in primary studies due to different types of intervention administered, different outcomes described and the low number of identified studies did not allow us to pool data together to produce a summary measure and to perform statistical evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…All studies that explored the effect of H. pylori eradication on iron absorption concluded that H. pylori infection is associated with a poorer response to oral iron therapy, that its treatment can enhance the efficacy of oral iron replacement therapy and that the screening for this infection should be considered in patients with unexplained or refractory iron deficiency anemia [4,8,16]. Results of the case series performed by Kotb et al (2012) [13] showed a statistically significant increase in haematological indices such as haemoglobin (Hb), serum ferritin (SF) and transferrin saturation (TF) achieved after H. pylori eradication compared to baseline at 6 and 12 weeks post therapy.…”
Section: H Pylori Eradication and Iron Absorptionmentioning
confidence: 99%